PENELITIAN TINDAKAN KELAS THINK PAIR SHARE UNTUK MATA PELAJARAN AKUNTANSI - Budi Mulyati; Kiki Ernawati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
The study was conducted to improve the result study in Accounting Subject used think pair share in SMK Al- Insan Cilegon. The study used classroom action research with two cycles. Each cycle encompased planning, implementing, observing and reflecting. The subject of the study were 48 students in class ten and teacher as a collaborator. The result showed that using think pair share could improve the results study up to 87,5% in second cycle.